Management of spontaneous septic hypothermia in intensive care. A national survey of French intensive care units - Eustache, Gabriel; Le Balc’h, Pierre; Launey, Yoann (Frontiers in Medicine, 2024)
The benefit of temperature control in sepsis or septic shock is still under debate in the literature. We developed a national survey to assess the current state of knowledge and the practical management of spontaneous septic hypothermia in French intensive care units. Out of more 764 intensivists who were contacted, 436 responded to the survey. The majority of doctors (52.4%) considered spontaneous septic hypothermia to be a frequently encountered situation in intensive care, and 62.1% were interested in this problem. Definition of spontaneous septic hypothermia among French intensivists was not consensual. More than half of the doctors questioned (57.1%) stated that they did not actively rewarm patients suffering from spontaneous septic hypothermia.